Respuesta :

Answer:

−x+43

Step-by-step explanation:

(5)(2)+33−x

=10+33+−x

Combine Like Terms:

=10+33+−x

=(−x)+(10+33)

=−x+43

thank me later! :⊃

Answer:

Step-by-step explanation:

-165    +    -1    =    -166

     -55    +    -3    =    -58

     -33    +    -5    =    -38

     -15    +    -11    =    -26

     -11    +    -15    =    -26

     -5    +    -33    =    -38

     -3    +    -55    =    -58

     -1    +    -165    =    -166

     1    +    165    =    166

     3    +    55    =    58

     5    +    33    =    38

     11    +    15    =    26

     15    +    11    =    26

     33    +    5    =    38

     55    +    3    =    58

     165    +    1    =    166